Reflection of Russian-Ukrainian military conflict in Indonesian and world Digital Media - Syurkani, Panca; Muzykant, Valerii L. (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
The military conflict between Russia and Ukraine occurred in February 2022, to be precise, on the 24th. This conflict was quite significant because it resulted in many civilians fleeing and damage to various public facilities. The Indonesian people participated in providing multiple comments related to this conflict related to the military, economy, politics, and law on human rights. Therefore, the researchers want to learn more about the Analysis of the Russo-Ukrainian military conflict in the Media, especially the Indonesian people's reaction to the media coverage. The research method used is descriptive qualitative. Data collection techniques were done by observing various Indonesian media containing comments about the Russian-Ukrainian military conflict. The data that has been collected will then be analyzed in depth to find out the results of the research, which states that the majority of Indonesian media say that many people are more supportive of Russia in taking action against Ukraine because NATO broke the agreement that was made before. Meanwhile, in terms of human rights, this conflict has committed several fakes as well as human rights violations, such as cases of sexual harassment, murders without prior trial, destruction of facilities, and so on, as stated in international human rights law as contained in the Universal Declaration of Human Rights article 3, Article 5, Article 6, Article 10, Article 13, Article 20, and so on. In addition, Indonesian people who are consumed by information write various negative comments smelling of defamation, also violating the rules regarding human rights as per the 1945 Constitution and the laws that apply in Indonesia.